RENDIMIENTO ACADÉMICO EN LAS ASIGNATURAS DE CIRUGÍA ORAL DE ESTUDIANTES DE ODONTOLOGÍA DE PREGRADO: UN ESTUDIO TRANSVERSAL - De Macêdo Santos, José Wittor (2025)
Objective: This study assessed the factors influencing the academic performance of undergraduate dental students in the field of oral surgery at a public university in southern Brazil. Materials and Methods: It included 146 students who were regularly enrolled in an undergraduate dental program, who completed at least one oral surgery subject. The survey questionnaire encompassed various variables, including sex, age, sexual orientation, family income, ethnicity, part-time employment, use of substance (licit or illicit), and whether dentistry was their initial choice for an undergraduate course. Academic performance was gauged using a grading system ranging from 0.0 (lowest possible grade) to 10.0 (highest possible grade). Bi- and multivariable linear regression analyses were performed to examine the associations between the outcome and independent variables. Results: An inverse relationship between age and academic performance remained significant (β: -0.318; 95% confidence interval [95%CI]: (-0.101–-0.034). Female students outperformed male students (β:0.173; 95%CI:0.022–0.400), while students who reported an increase in drug use exhibited lower academic performance (β: -0.158; 95% CI: -0.354–-0.001). Conclusions: It was concluded that academic performance in oral surgery subjects was notably poorer in older students and those who reported increased drug use. Female students, on the other hand, demonstrated better academic performance.